Chemical assessment, antioxidant and antimicrobial of leafs extracts of Virola sebifera, an Amazonian medicinal plant (Research, Society and Development, 2021)
The high biodiversity of Amazon forest implies in a great number of plants with ethnopharmacological utilization. V. sebifera is one of the most important species of Virola genus, used in treatment of rheumatism, arthritis, dyspepsia, malaria, muscle pain and erysipelas. This study aimed to investigate its chemical composition, antioxidant and antimicrobial properties. For this, leafs extracts i) 70% ethanol in ultrasound bath (CEU); ii) 70% ethanol in Soxhlet (CES); and iii) sequential extraction in Soxhlet apparatus, starting with hexane (HE), followed by methanol (ME), and 70% ethanol extract (EE). Phenolic concentration, total flavonoid and antioxidant activity were assessed. The highest phenolic and total flavonoid contents were found in CEU and EE showed the best antioxidant activity. The most relevant substances identified by GC-MS analysis were the Kusunokinin, Hinokinin and catechol, among others first time related in V. sebifera. The antimicrobial activity was tested against Staphylococcus aureus, S. epidermidis, Salmonella typhimurium, Escherichia coli, and Candida albicans. The CEU, CES, EM, and EE obtained positive results against S. aureus and S. epidermidis. CES and EM also inhibited S. typhimurium and E. coli. Based on these results, V. sebifera can be recognized as a promising source of antioxidant and antimicrobial compounds.